1975
DOI: 10.1128/jvi.16.6.1357-1366.1975
|View full text |Cite
|
Sign up to set email alerts
|

Thymineless bacteriophage induction in Staphylococcus aureus. I. High-frequency transduction with lysates containing a bacteriophage related to bacteriophage phi 11

Abstract: A thymine-requiring mutant of Staphylococcus aureus, strain 8325(PIM)thy, undergoes prophage induction and lysis after thymine starvation. Four different phages were isolated from the lysate in low titers, among which was a phage designated 414, which differs from phage 441 in its immunity locus. The thymineless induced lysates of strain 8325(PIn8)thy transduce the penicillinase plasmid at high frequency (10-1), whereas transduction of chromosomal markers is inefficient. A plasmid-cured derivative of strain 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…e Less than the given frequency denotes that no transfectants were detected. nism (lysogenic for 4)11, 412, and 4)13) contains a predominance of 4)12 (26), we expected the medium from 8325(N)nov also to contain a predominance of 4)12; however, because of the high competence-conferring activity of the 8325(N)nov growth medium, a significant number of free 4)11 virions also were expected. However, when 8325(N)nov growth medium was treated with 4)12 antiserum at 35°C for 30 min and assayed for lytic activity toward 8325-4, only 10 PFU/ml could be detected ( Table 3).…”
Section: Resultsmentioning
confidence: 94%
“…e Less than the given frequency denotes that no transfectants were detected. nism (lysogenic for 4)11, 412, and 4)13) contains a predominance of 4)12 (26), we expected the medium from 8325(N)nov also to contain a predominance of 4)12; however, because of the high competence-conferring activity of the 8325(N)nov growth medium, a significant number of free 4)11 virions also were expected. However, when 8325(N)nov growth medium was treated with 4)12 antiserum at 35°C for 30 min and assayed for lytic activity toward 8325-4, only 10 PFU/ml could be detected ( Table 3).…”
Section: Resultsmentioning
confidence: 94%
“…Thus, it was concluded that the prophage is necessary for the expression of competence in strain 8325 (Sjostrom et al, 1973). Besides #11, only lysogens carrying the closely related phages 83A (Sjostrom and Philipson, 1974) and 4il4 (Rudin and Lindberg, 1975) could demonstrate competence. The origin of the latter phage is unclear, but phages <J)11 (Novick, 1967), 83A (Wentworth, 1963) and (j)14 (Rudin and Lindberg, 1975) all belong to the serological group B; therefore, they all are morphologically related.…”
Section: + 2+mentioning
confidence: 99%
“…Besides #11, only lysogens carrying the closely related phages 83A (Sjostrom and Philipson, 1974) and 4il4 (Rudin and Lindberg, 1975) could demonstrate competence. The origin of the latter phage is unclear, but phages <J)11 (Novick, 1967), 83A (Wentworth, 1963) and (j)14 (Rudin and Lindberg, 1975) all belong to the serological group B; therefore, they all are morphologically related. Sjostrom et al (1973) also demonstrated that vegetative (j)ll could confer competence to 8325-4.…”
Section: + 2+mentioning
confidence: 99%
See 2 more Smart Citations